The theory of discretionary behavior implication for business and educational administration - Poblador, Niceto S. (The Philippine Review of Business and Economics, 1995)
Drawing on insights from organizational economics, this paper attempts to explain certain bureaucratic phenomena that have long been outside the purview of economics. It shows that "rational" behavior on the part of the various groups in economic organizations such as business firms and educational institutions preclude the attainment of the traditional goal of profit maximization. The inescapable conclusion is that the analysis of organizational behavior and indeed, the very notion of optimality of the firm, requires more complex objective functions than what we have long been accustomed to.